2014
DOI: 10.1521/jscp.2014.33.5.428
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evidence that Thoughts of Thwarted Belongingness Mediate the Relations Between Level of Attachment Insecurity and Depression and Suicide-Related Thoughts in Inpatient Adolescents

Abstract: there are well-documented associations between adolescent depression, suicide-related thoughts, and interpersonal functioning, which include identified relations between these variables and insecure attachment. Dykas and Cassidy (2011) recently reframed traditional attachment theory into a social information processing model in which early caregiver experiences produce secure or insecure attachment-related schemas which, in turn, lead to biased social information processing. this model echoes beck's cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 39 publications
(54 reference statements)
1
27
2
Order By: Relevance
“…Surprisingly, however, family support was not significantly associated with either of the suicide-specific outcomes. This contradicts other findings that have linked higher levels of family support and attachment with lowered risk of suicidal thoughts and behaviors among adolescents (Maimon, Browning, & Brooks-Gunn, 2010;Sheftall, Schoppe-Sullivan, & Bridge, 2014;Venta, Mellick, Schatte, & Sharp, 2014) as well as studies that have found that family-based interventions focused on repairing attachment (Diamond, Russon, & Levy, 2016) and improving family communication (Asarnow, Berk, Hughes, & Anderson, 2015;Pineda & Dadds, 2013;Wharff, Ginnis, & Ross, 2012) are effective at reducing suicidal symptoms among adolescents. It is possible that because parental support was only measured at Wave I, the models were unable to account for the impact of changing parental support over time.…”
Section: Discussioncontrasting
confidence: 79%
“…Surprisingly, however, family support was not significantly associated with either of the suicide-specific outcomes. This contradicts other findings that have linked higher levels of family support and attachment with lowered risk of suicidal thoughts and behaviors among adolescents (Maimon, Browning, & Brooks-Gunn, 2010;Sheftall, Schoppe-Sullivan, & Bridge, 2014;Venta, Mellick, Schatte, & Sharp, 2014) as well as studies that have found that family-based interventions focused on repairing attachment (Diamond, Russon, & Levy, 2016) and improving family communication (Asarnow, Berk, Hughes, & Anderson, 2015;Pineda & Dadds, 2013;Wharff, Ginnis, & Ross, 2012) are effective at reducing suicidal symptoms among adolescents. It is possible that because parental support was only measured at Wave I, the models were unable to account for the impact of changing parental support over time.…”
Section: Discussioncontrasting
confidence: 79%
“…Chen et al (2012) found a positive relationship between insecure attachment and social disconnection in adolescents in their study. In other studies, significant-level relationships were found between attachment styles and need for belongingness (Chen, Hewitt, & Flett, 2015;Greenwood & Long, 2011;Leary, Kelly, Cottrell, & Schreindorfer, 2013;Venta, Mellick, Schatte, & Sharp, 2014).…”
mentioning
confidence: 72%
“…Each item is rated on a 0-3 scale and, thus, total scores range from 0-63. The internal consistency, factor structure, and validity of BDI-DEPRESSION, SUICIDE, AND EMOTIONAL TRUST 8 II have been previously evaluated (Beck et al, 1996) and the measure has been used with adequate validity among inpatient adolescents (e.g., Cronbach's alpha = .92 in Grover, Green, Pettit, Monteith, Garza, & Venta, 2009 and Cronbach's alpha = .92 in Venta et al, 2014). In the present study, Cronbach's alpha for the BDI-II was .930.…”
Section: Methodsmentioning
confidence: 99%
“…Joiner's interpersonal-psychological theory of suicidal behavior (2005), a widely accepted conceptualization of suicide risk, suggests that the desire for death is driven by negative interpersonal beliefs (i.e., perceived burdensomeness and thwarted belongingness). Venta and colleagues (Venta, Mellick, Schatte, & Sharp, 2014) built upon Joiner's (2005) theory, by demonstrating that, in inpatient adolescents, these negative interpersonal beliefs are associated with depression, suicide-related thoughts, and maternal attachment insecurity-providing tentative evidence that insecure attachments produce interpersonal beliefs that, in turn, increase vulnerability for depression and suicide-related thoughts in teens. In the context of these models, the findings of the present study suggest that perhaps emotional trust beliefs in mothers serve as an antidote to the interpersonal beliefs implicated in both models (i.e., perceived burdensomeness and thwarted belongingness).…”
Section: Depression Suicide and Emotional Trust 11mentioning
confidence: 99%
See 1 more Smart Citation